Transfer of genes and translocations from Neurospora crassa to N. tetrasperma - David D. Perkins (Fungal Genetics Reports, 1991)
It is difficult to obtain progeny when N. crassa and N. tetrasperma are intercrossed directly. Metzenberg and Ahlgren (1969 Neurospora Newsl. 15:9-10; 1973 Can. J. Genet. Cytol. 15:571-576) developed a transfer kit of interspecific hybrids which they used for bridging-crosses that enabled them to move the mating type genes from N. tetrasperma into N. crassa. I have recently been concerned with introgressing mutant genes and translocations from N. crassa into N. tetrasperma, and have found their strain C4,T4 a (FGSC 1778) extremely useful for the initial cross, and more fertile than other members of the kit.